2022
DOI: 10.1186/s12979-021-00257-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of immunity markers with the risk of incident frailty: the Rugao longitudinal aging study

Abstract: Background The neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and systemic immune-inflammation index (SII) are readily available circulatory immunity markers that are associated with components of frailty. However, few studies have investigated the relationship between these immunity markers and frailty, and it remains unknown whether they are predictive of incident frailty in older adults in general. Hence, we aimed to examine the association of these immunity markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In addition to the healthspan parameters focused on in this review, there are further health assessments that can be useful in intervention studies in aging mice. These include blood chemistry analysis, which provides information on glucose homeostasis, lipid metabolism, liver and kidney function, and inflammatory markers ( O’Connell et al, 2015 ; Palliyaguru et al, 2021a ; Zhang et al, 2022 ). Live animal imaging techniques, such as magnetic resonance imaging (MRI) ( Chen et al, 2011 ) and positron emission tomography (PET) ( Borrás et al, 2011 ; Hulsmans et al, 2018 ), can allow for the non-invasive visualization of organs and tissue and can therefore provide insights into structural and functional changes occurring with an intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the healthspan parameters focused on in this review, there are further health assessments that can be useful in intervention studies in aging mice. These include blood chemistry analysis, which provides information on glucose homeostasis, lipid metabolism, liver and kidney function, and inflammatory markers ( O’Connell et al, 2015 ; Palliyaguru et al, 2021a ; Zhang et al, 2022 ). Live animal imaging techniques, such as magnetic resonance imaging (MRI) ( Chen et al, 2011 ) and positron emission tomography (PET) ( Borrás et al, 2011 ; Hulsmans et al, 2018 ), can allow for the non-invasive visualization of organs and tissue and can therefore provide insights into structural and functional changes occurring with an intervention.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one other study has investigated the relationship between SII and frailty. Zhang et al [21] analyzed data from 1,822 older adults in the Rugao Longitudinal Aging Study, revealing that those with higher baseline SII levels (fourth quartile) faced over a twofold increase in the risk of developing frailty compared to those in the lowest SII quartile ( rst quartile). That study employed Fried's frailty phenotype [32] to categorize the frailty status of participants.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Subsequent research has expanded its applicability beyond cancer to include patients undergoing surgery, individuals with intracerebral hemorrhage, and those with acute coronary syndrome. [11][12][13][14][15][16][17][18] Numerous studies have demonstrated the integral role of in ammation in the pathogenesis of frailty, highlighting signi cant associations between frailty and elevated levels of in ammatory markers such as C-reactive protein (CRP), [19] interleukin-6 (IL-6), [20] neutrophil-lymphocyte ratio (NLR), [21] and white cell count. [22] SII, calculated based on peripheral lymphocyte, neutrophil, and platelet counts, is postulated to offer a more comprehensive representation of both local immune response and systemic in ammation.…”
mentioning
confidence: 99%
“…A recent 2-yr longitudinal study assessed the neutrophil-to-lymphocyte ratio (NLR) and systemic inflammation index (SII), as indicators of immunesenescence, in 1,822 older adults for their association with incident frailty, using the physical frailty phenotype. Both log NLR and log SII were positively associated with incident frailty; the association remained when adjusted for multimorbidities ( 255 ). In contrast, a 5-yr longitudinal study in 657 >85-yr-old subjects found no association of T-cell senescence with loss of muscle function or prevalent or incident sarcopenia ( 256 ).…”
Section: The Physiological Phenotype Of Frailtymentioning
confidence: 99%